Theoretical model of recovery following a suicidal episode (COURAGE): scoping review and narrative synthesis. Issue 6 (17th November 2022) - Sokol, Yosef; Levin, Chynna; Linzer, Mairav; Rosensweig, Chayim; Hubner, Shifra; Gromatsky, Molly; Walsh, Samantha; Dixon, Lisa; Goodman, Marianne
Abstract : Background: Despite a significant need, there are currently no rigorously developed empirically based models for what personal recovery from a suicidal episode looks like. Aims: To develop a theoretical model of personal recovery after a suicidal episode, based on a comprehensive literature review and stakeholder feedback. Method: A scoping review of all empirical studies on this topic was conducted, followed by a thematic analysis to create a preliminary framework. Consultation-based revisions were then made based on feedback from a stakeholder panel to develop the final theoretical model. Results: The final model comprised seven themes: choosing life, optimising identity, understanding oneself, rediscovering meaning, acceptance, growing connectedness and empowerment (acronym 'COURAGE'). Although there are some similarities between COURAGE and other models of personal recovery, there are components, such as 'choosing life' and 'understanding oneself', that are specific to recovery after an acute suicidal episode. Conclusions: To our knowledge, this is the first study to use a comprehensive literature review with stakeholder feedback to develop a conceptual model of personal recovery after an acute suicidal episode. This model has important implications for both researchers and clinicians to consider. Looking ahead, COURAGE can inform the reconceptualisation of assessment, research and clinical care of individuals who have experienced a suicidal episode.